The Ethnoscience Study on Eucalyptus Oil Distillation in Buru Island as a Source for Learning Chemistry - Muhammad Rizal Hardiansyah; Rahmiati Darwis; Nur Hikmah (Chemistry Education Department, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga, 2024)
Chemistry is a branch of science closely related to daily life. Ethnoscience cannot be separated from science, especially in the study of chemistry. The tradition of distilling eucalyptus oil (Melaleuca cajuputi) on Buru Island has been carried out traditionally for generations. This research aims to analyze and reconstruct the indigenous knowledge of the community in the eucalyptus oil distillation process into scientific knowledge that can be used as a source for learning chemistry. This research used a qualitative approach based on ethnoscience with interview, observation, and documentation methods. Data analysis employs the Miles-Huberman model, which consists of data reduction, data presentation, conclusion drawing, and verification. The results of the research showed that the eucalyptus oil distillation process can be explored in science materials or concepts related to separation techniques, differences in density, phase changes, and substance pressure. The ethnoscience study results indicated the potential of ethnoscience to be applied in chemistry education.